Borders (The Netherlands) - Abbenhuis, Maartje (1914-1918-online. International Encyclopedia of the First World War, 2014)
The borders of the Netherlands were an important site of war experience for the Dutch, as well as a contested site of war interaction for the belligerents.
Keywords: Elektrozaun; Erster Weltkrieg; Neutralität

Where war met peace. The borders of the neutral Netherlands with Belgium and Germany in the First World War, 1914–1918 - Abbenhuis, Maartje (Journal of borderlands studies, 2007)
„In wartime, neutral territory beckons as a beacon of safety from the conflict and strife. This was especially true for the neutral Netherlands in the First World War (1914–1918), which was situated within a short distance of the Western Front and was bordered by belligerent Germany and German‐occupied Belgium. The Dutch land border became the country's most important neutrality frontier, functioning as the geographical place where neutrality began and ended, which necessitated increased border security, witnessed new border‐crossing activities, and ensured that life for border residents changed dramatically. This paper illustrates that, once Germany occupied Belgium, the Dutch border region in the south became a fraught zone between ‘war’ and ‘peace.’ But the eastern border with Germany proper also changed in character. The war situation and changing circumstances at the frontier impacted on the relationship between locals and the state (the authority in charge of border security) and changed locals’ understandings about what it meant to be ‘neutral,’ a ‘frontier‐zone resident,’ and ‘Dutch’ in this extraordinary situation.“
Keywords: Erster Weltkrieg; Neutralität; Staatsgrenze

Neutral-Moresnet. Ein Dorf ohne Staatszugehörigkeit (1815–1915) - Pabst, Klaus (150 Jahre Regierung und Regierungsbezirk Aachen. Beiträge zu ihrer Geschichte, 1967)
Keywords: Moresnet (Autonomes Gebiet); Neutralität